Hakikat Agama Dalam Pembentukan Karakter Anak Usia Dini - Nurma Nurma; Maemonah Maemonah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
Religion has a big influence in shaping the character of the nation's children. Children's character can be formed from an early age through a continuous education process. The direction of education is to humanize humans. Humans cannot be separated from education as well as education, the two are interconnected, will function if they are not separated. Educational actions are directed at humans to develop the potentials that already exist in them, namely the potential to do good. Teaching to children includes the values of religious teachings, namely the values of aqidah, values of worship, moral values. The purpose of practicing religious values is to form a positive character from an early age. Achievement of teaching can be implemented using various learning methods. The current phenomenon of the role of educators in inculcating teaching values is still low, this can be seen where children are still not able to apply the values of religious teachings in behavior. True moral investment must start early as the initial formation of future capital. Keywords: Religion, Character, Early Childhood References Abror, R. H. (2013). RELASI PENDIDIKAN DAN MORALITAS DALAM KONSUMSI MEDIA ; PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM. Jurnal Pendidikan Islam, 401–418. Ainiyah Nur, & Wibawa, N. H. H. P. (2013). PEMBENTUKAN KARAKTER MELALUI PENDIDIKAN AGAMA ISLAM. Jurnal Al-Ulum, 13, 25–38. Ananda, R. (2017). Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini Implementasi Nilai-nilai Moral dan Agama pada Anak Usia Dini. 1(1), 19–31. https://doi.org/10.31004/obsesi.v1i1.28 Cahyaningrum, E. S., Sudaryanti, & Purwanto, N. A. (2017). PENGEMBANGAN NILIA-NILAI KARAKTER ANAK USIA DINI MELALUI PEMBIASAAN DAN KETELADANAN. 6, 203–213. Helmawati. (2015). Mengenal dan Memahami PAUD. Remaja Rosdakarya. Hidayat, A. (2018). METODE PENDIDIKAN ISLAM UNTUK GENERASI MILLENNIAL. FENOMENA : Jurnal Penelitian, 10(1), 55–76. Ibda, F. (2012). PENDIDIKAN MORAL ANAK MELALUI. Jurnal Ilmiah DIDAKTIKA, XII(2), 338–347. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Istiadie, Johan, Subhan, F. (2013). Pendidikan Moral Perspektif Nasih Ulwan. Jurnal Pendidikan Agama Islam, 1, 47–60. Jadid, N. (2017). PERAN AGAMA DAN PENDIDIKAN AGAMA ISLAM. 04(02), 120–133. Jannah, R. R. (2016). Internalisasi Nila-Nilai Agama pada Anak Usia Dini Melalui Redesain Masjid Besar Jatinom Klaten. Jurnal A-Athfal: Jurnal Pendidikan Anak, 2(1), 15–28. https://doi.org/2477-4715 : 2477-4189 Juanda. (2019). Pendidikan Karakter Anak Usia Dini melalui Sastra Klasik Fabel Versi Daring. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 39–54. https://doi.org/10.31004/obsesi.v3i1.126 Khomsiyatin, Iman, N., & Ariyanto, A. (2017). Metode Pendidikan Akhlak Pada Anak Usia Dini di Bustanul Athfal Aisiyah Mangkujayan Ponorogo. Jurnal EDUCAN, 2(3), 272–281. Kristiawan, M. (2016). Filsafat Pendidikan The Choice Is Yours. Valia Pustaka. Kurniawan, A. T. (2010). Perkembangan jiwa agama pada anak. 69–80. Kusumawati, I. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 139–148. Munawaroh, A. (2019). Keteladanan Sebagai Metode Pendidikan Karakter. Jurnal Penelitian Pendidikam Islam, 7(2). Nadjih, D., & Imroatun, I. (2016). Hadits Tentang Pendidikan Jasmani Anak Usia Dini. Prosiding Seminar Nasional Peran Pengasuhan Anak Raudhatul Atfal Dalam Membangun Karakter Bangsa, 51–64. http:// repository.uinbanten.ac.id/1420/9/09 - Prosiding PGRA - Difla Nadjih.pdf Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Nurrohmah, R., & Syahid, A. (2020). Tujuan Pendidikan Perspektif Al-Quran dan Pendidikan Barat. Attractive: Innovative Education Journal, 2(2). Rahma, Z., & Maemonah, M. (2021). Filsafat Behaviorisme Dalam Pendidikan Anak Usia Dini Perspektif Rudolf Steiner. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 29–40. https://doi.org/10.32678/AS-SIBYAN.V6I1.2616 Ratnawati. (2016). Memahami Perkembangan Jiwa Keagamaan. Jurnal Kajian Keislaman Dan Kemasyarakatan, 1(1). Risnawati, Atin, Priyantoro, eka D. (2021). Pentingnya penanaman nilai-nilai agama pada pendidikan anak usia dini dalam perspektif al-quran. As-Sibyan, Jurnal Pendidikan Anak Usia Dini, 6(1), 1–16. Saihu. (2019). Konsep Manusia dan Implementasinya dalam Perumusan Tujuan Pendidikan Islam Menurut Murtadha Muthahhari. ANDRAGOGI JURNAL PENDIDIKAN ISLAM, 1(2), 197–217. Santoso, F. S. (2020). Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 13–22. https://doi.org/10.47200/jnajpm.v5i1.418 Setiani, & Nadjih, D. (2016). Pembentukan Karakter Anak Usia Dini Melalui Pendidikan Agama Islam Di TK ABA Kalibulus Rogobangsan Bimomartani Ngemplak Sleman. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 6(2), 125–136. Siti Khasinah. (2013). Hakikat Manusia MenurutPandangan Islam dan Barat. Jurnal Ilmiah DIDAKTIKA, XIII(2), 296–317. Syafe’i, I. (2015). TUJUAN PENDIDIKAN ISLAM. Al-Tadzkiyyah: Jurnal Pendidikan Islam, 6(November), 151–166. Zahroh, S., Pendidikan, P., Raudhatul, G., Islam, U., & Sunan, N. (2020). Peran lingkungan sosial terhadap pembentukan karakter anak usia dini di jogja green school. 7(April).